Rotor Speed Control Maximum Power Point Tracking for Small Wind Turbine - Ni Luh Dharmaraditya; Lazarus Stefan; Feri Yusivar (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Due to the change of energy source to renewable energy, the trend of wind turbine is increased in last 5 years. Small Wind Turbine that convert kinetic energy to electric energy needs a rectifier to convert AC to DC. Rectifier used in this paper is active rectifier. Because of its power characteristics, wind turbine needs maximum power point tracking (MPPT) to track its maximum power. This paper shows that by using active rectifier, the algorithm of tracking a maximum power able to be tracked by controlling its rotor angular speed. The simulation result proves that the speed control and MPPT algorithm, perturb and observe, is able to be implemented in various wind speed.